2019
DOI: 10.1080/21505594.2019.1584027
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy plays a protective role against Trypanosoma cruzi infection in mice

Abstract: Autophagy is a catabolic pathway required for cellular and organism homeostasis. Autophagy participates in the innate and adaptive immune responses at different levels. Xenophagy is a class of selective autophagy that involves the elimination of intracellular pathogens. Trypanosoma cruzi is the causative agent of Chagas, a disease that affects 8 million individuals worldwide. Previously, our group has demonstrated that autophagy participates in the invasion of T. cruzi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
6
18
0
Order By: Relevance
“…This is also observed in other cardiomyopathies, that autophagy is upregulated in connective tissue, organizing cardiac remodeling [32,33]. Besides, the evaluation of autophagy in splenocytes and cardiac T cells corroborates the higher activation of this process in T cells from infected mice, also in effector CD44 high T cells, which implies that in vivo infection is also an autophagy inducer, as recently shown by immunoblot-ting using the liver of infected animals [17,25]. As described in in vitro studies, the pathogen can induce autophagy, upregulating LC3 and other autophagy genes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is also observed in other cardiomyopathies, that autophagy is upregulated in connective tissue, organizing cardiac remodeling [32,33]. Besides, the evaluation of autophagy in splenocytes and cardiac T cells corroborates the higher activation of this process in T cells from infected mice, also in effector CD44 high T cells, which implies that in vivo infection is also an autophagy inducer, as recently shown by immunoblot-ting using the liver of infected animals [17,25]. As described in in vitro studies, the pathogen can induce autophagy, upregulating LC3 and other autophagy genes.…”
Section: Discussionsupporting
confidence: 77%
“…First, we evaluated if autophagy in cardiac fibers is upregulated in vivo after T. cruzi infection, as observed in the liver [17,25], and in vitro in different lineage cells by others [26,28,29]. To this end, the mice were infected and the presence of LC3 puncta was investigated by immunostaining in cardiac ventricles sections ( Fig.…”
Section: Autophagy Is Upregulated During Chagasic Cardiomyopathy In Vivomentioning
confidence: 99%
“…The infection, cell necrosis and associated inflammatory signalling result in the activation of a range of innate effector mechanisms. There is some evidence from analysis of Beclin‐1‐deficient mice that host cell autophagy can provide some marginal early restraint on parasite replication 82 . Epimastigotes are complement‐sensitive but trypomastigotes have effective molecular mechanisms providing resistance to complement‐mediated lysis 83 .…”
Section: Stage 1: T Cruzi Systemic Colonization and Innate Responsesmentioning
confidence: 99%
“…Numerous studies demonstrated that autophagy could be triggered during microbial infection, such as bacteria, viruses, protozoa, and parasitic helminths [ 20 23 ]. However, autophagy induction has not been confirmed in Trichinella infection.…”
Section: Discussionmentioning
confidence: 99%